Pengembangan Model Pembelajaran Project Based Learning pada Mata Kuliah Computer Aided Design - Endar Nayono, Satoto; ER, Nuryadin (Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
One of the key competencies of graduates majoring in Civil Engineering and Planning Education, Faculty of Engineering, Yogyakarta State University (YSU) is able to plan buildings. CAD courses aim to train students to be able to pour the planning concepts into the picture. One of the obstacles faced in the course are concepts and pictures that created by the students often do not correspond to the standards used in the field. This study aims to develop a model of project-based learning so that the students’ pictures are more in line with the actual conditions in the field. This study was carried out through the stages as follows: (1) Pre test, (2) Planning of learning, (3) Implementation of the learning model of project-based learning, (4) monitoring and evaluation (5) Reflection and revision, (6) Implementation of learning in the next cycle, and (7) Evaluation of the learning outcomes. This study was conducted for four months in 2012 in the Department of Civil Engineering and Planning Education, Faculty of Engineering, YSU. The subjects of this study are the students who took the course of Computer Aided Design. The analysis of the data used descriptive qualitative and descriptive statistics. The results of this study were: (1) The implementation of project based learning model was proven to increase the learning process and the learning outcomes of students in the subject of CAD through the provision of buildings planning pictures tasks of school buildings based on the real conditions in the field. The task was delivered in every meeting and improved based on the feedback from their lecturers, (2) the learning model of project based learning will be easier to be implemented if it is accompanied by the model of peer tutoring and the learning model of PAIKEM.